Concept of unbearable suffering needs to be better understood by nurses - Pinto, Sara (My University, 2023)
The study starts with the discussion about the legalisation of euthanasia in Spain, and aims to analyse the concept of U-Suffering as a foundation for the development of a new nursing diagnosis.1 Suffering is deeply connected with human existence, and its relief is a pivotal outcome for nurses and other healthcare providers. However, the assessment of a patient’s suffering (and whether it is unbearable) is one of the most difficult requirements to form a judgement on.
Keywords: Euthanasia